Energy poverty in the face of armed conflict: The challenge of appropriate assessment in wartime Syria. (January 2023) - Alhaj Omar, Fuad; Mahmoud, Ibrahim; Cedano, Karla G.
Abstract: As a result of the ongoing war in Syria, most of the infrastructure for the generation, transmission and distribution of energy has been destroyed. At the same time, energy sources have come under the control of various foreign powers. Although access to energy is considered a basic human right, it has been neglected in Syria because the focus has been on immediate needs such as food and health. Also, there are no official estimates for energy poverty at the national level. This study is considered the first attempt to estimate household energy poverty during the crisis and compare it with the situation before 2011. This provides the necessary support to understand the severity of energy poverty. The field investigation is a questionnaire survey carried out in 35 residential communities located in North and Northwest Syria. In addition to using some of the existing income/expenditure ratio measurement approaches, the multidimensional energy deprivation index (MEDI) is computed to analyze energy poverty in multiple dimensions such as access to electricity, clean cooking, heating fuel, and the inability to obtain a reliable and adequate amount of different energy services. Results show that energy poverty is 20 to 70 times higher than <8 years ago. Most importantly, we can focus on the energy services that are most important for the inhabitants of these regions. This will certainly help in the design of aid programs and public policies that foster a better quality of life for the inhabitants of these conflict regions.